The Generalized Backstepping Control Method for Stabilizing and Solving Systems of Multiple Delay Differential Equations - Fadhel, Fadhel S; Noaman, Saja F (Al-Nahrain Journal of Science, 2018)
In this paper, a generalized approach of the backstepping method for stabilizing and solving system of ordinary differential equations will be applied for systems of differential equations with multiple delay by transforming the non-linear system of delay differential equations into a system of ordinary differential equations with cooperation of the method of steps. The basic idea of this approach is to find Lyapunov function for stabilizing the system of different time steps which is chosen as the definitions of the present approach.